Analisis Efektivitas Pada Cooling Tower Menggunakan Metode Oee PT XYZ - Condro Hariseto; Tjahyono, Rudi (Universitas Muhammadiyah Sorong, 2026)
The cooling fan in a geothermal power plant’s cooling tower is vital for maintaining temperature stability, and its performance directly affects efficiency and reliability. This study evaluates the cooling fan at PT XYZ using the Overall Equipment Effectiveness (OEE) method and identifies operational losses through the Six Big Losses framework. Research was conducted via field observation, interviews with technicians and operators, and data collection on operating time, downtime, performance, and cooling quality. Results show Availability at 98.75%, Performance at 97.21%, and Quality at 88.89%, producing a total OEE of 90.83%, which surpasses the world-class benchmark of 85%. Despite this strong performance, Six Big Losses analysis revealed significant issues from Defect/Process Losses and Reduced Speed Losses, both impacting cooling quality. These findings indicate that while the cooling fan’s effectiveness is very good, improvements are still needed to enhance quality and operational stability. Practically, the study provides guidance for companies to design more targeted maintenance strategies, while academically, it serves as a reference for further research on industrial equipment effectiveness using OEE and Six Big Losses.